Nanoscaled bioactive glass particles and nanofibers - Taygun, M. Erol; Boccaccini, Aldo R. (Elsevier Inc., 2017)
Nanoscale bioactive glasses of silicate composition are gaining increasing attention due to their superior bioactivity, enhanced osteoconductivity and antibacterial properties when compared to conventional (micron-sized) bioactive glasses. In this Chapter, we present an overview of the technology, characterization, and applications of nanoparticle and nanofibrous bioactive silicate glasses. Novel fabrication technologies are presented, covering sol-gel routes, microemulsion techniques, gas phase synthesis method (flame spray synthesis), laser spinning and electrospinning, and the synergistic effects that determine the final properties of these materials. The advantages of nanoscaled bioactive glasses compared to conventional bioactive glasses are also discussed based on available literature evidence. The focus of the Chapter is in the diverse application areas of nanoscale bioactive glasses ranging from tissue engineering scaffolds to drug delivery and dentistry, considering also polymer/bioactive glass nanocomposites as promising materials for implants, bone fillers, and bioactive coatings for orthopedic applications. The nanofeatures characteristic of this type of bioactive glasses are discussed and the possibilities to expand the use of these nanomaterials in other nanotechnology approaches aiming at advanced biomedical applications (nanomedicine) are also highlighted.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Bioactive glass coatings; Bioactive glass nanofibers; Bioactive glass nanoparticles; Nanocomposites; Nanomedicine; Tissue engineering